Analyzing Students' Misconceptions Based on Submicroscopic Level Representation in Elements, Compounds, and Mixtures - Arum Dwisetyo Arini; Utiya Azizah; Sukarmin; Muhammad Satriawan; Hanandita Veda Saphira (Postgraduate, University of Mataram, 2025)
The aim of this study is to analyze misconceptions at the submicroscopic level as well as the causal factors of misconceptions in elemental, compound and mixture materials. This research was conducted using descriptive-quantitative method using three-tier diagnostic test and interview. The research subjects were grade IX with 41 students in a junior high school in Malang. The results of this study indicate that 31.0% of students experience misconceptions in determining the concept of atoms, especially for like and unlike atoms in determining elements, compounds and mixtures, 29.0% in the difference in material changes when viewed from the shape of atoms owned, and 27.0% in changes in the constituent particles of elements, compounds and mixtures. The factors causing this misconception are based on the way of learning, misconceptions from teachers, learning methods, initial abilities, and supporting books. The conclusion of this research is that students experience misconceptions that have an impact on their understanding of concepts, especially for the submicroscopic level. The ability to understand the submicroscopic level which is still low causes the need for efforts in reducing the misconceptions that occur.